Examining the effects of teacher self-compassion, emotion regulation, and emotional labor strategies as predictors of teacher resilience in EFL context - Hu, Yan (Frontiers in Psychology, 2023)
This study aimed to examine the effects of teacher self-compassion, emotion regulation, and emotional labor strategies on teacher resilience in the English as a foreign language (EFL) context. A sample of 711 Chinese EFL teachers participated in the study. Confirmatory factor analysis (CFA) was run to assess the psychometric properties of the instruments, and structural equation modeling (SEM) was employed to evaluate the relationships between variables. The results showed that teacher self-compassion and emotional labor strategies directly predicted teacher resilience. Furthermore, teacher emotion regulation indirectly predicted teacher resilience via the mediation of emotional labor strategies. These findings suggest that interventions targeting teacher emotional regulation and self-compassion may be effective in promoting teacher resilience in the EFL context.